An Interdisciplinary Methodology for the Characterization and Visualization of the Heritage of Roadway Corridors1. Issue 4 (23rd July 2016) - Loren‐Méndez, Mar; Mata‐Olmo, Rafael; Ruiz, Rita; Pinzón‐Ayala, Daniel
Abstract: Roads, particularly since the advent of motorized traffic, have hugely impacted contemporary landscapes. Although their significance was noted in the 1980s, specific roadway‐heritage studies are scarce. Research in different disciplines has identified certain features of roads, but an integrated approach to roadway heritage or a consensus on what this constitutes are lacking. This article proposes an interdisciplinary methodology to assess roadway heritage. Roadways are interpreted within the framework of semantic openness that currently characterizes heritage studies, territory being the basic element of interpretation. Rather than a fragmented approach to conservation, the research defines integrated heritage configurations where natural, cultural, and historical features combine to produce a cohesive form of heritage. GIS (Geographical information systems) technology is used with an online database to assess the complexity of roadway heritage. ICT (Information and communications technology) strategies to raise public awareness are outlined. The methodology is applied to assess the historical N‐340 Mediterranean roadway corridor in Spain.